Polymerization-Induced Direct Photolithography of Quantum Dots - Kim, Taehyung; Gwak, Namyoung; Oh, Nuri; Kim, Tae Ann (John Wiley & Sons Ltd., 2025)
The development of high-resolution displays has driven the exploration of quantum dot (QD)-based patterning techniques, ranging from inkjet printing to direct photolithography. Among these methods, direct photolithography stands out as a promising technique for creating high-resolution QD patterns without the need for a photoresist layer. This approach relies on photochemical reactions that induce solubility changes in target materials when exposed to specific wavelengths of light. While various patterning strategies have been reported, polymerization-induced network formation offers a straightforward yet effective approach for fabricating QD patterns, simultaneously inheriting the advantageous physical and chemical properties of polymers. This review categorizes and discusses the photochemical reactions that enable polymerization according to their underlying mechanisms. Recent examples utilizing these reactions for direct photolithography of QDs are classified and summarized based on reactive functional groups-alkene, alkane, alkyne, and disulfide-involved in the polymerization process. Finally, we propose future directions for advancing this technology, including improvements in material compatibility, device integration, and the introduction of new functionalities, which could further expand the potential applications of QD-based optoelectronic devices.